(untitled) (PerCursos, 2025)
This study investigated the implementation of a didactic sequence focused on the Caminhos dos Cânions do Sul Geopark, using concepts of geoeducation and active teaching methodologies in the context of high school education. The research was applied to a 3rd-year class at the Jacinto Machado State Basic School in Santa Catarina in 2023. The objective was to encourage critical thinking, creativity, and reflection on the interaction between society, environment, and geodiversity. The didactic sequence included activities such as field classes, geoeducational games, and the creation of informative posters. The active methodologies employed were Microlearning, Team-Based Learning, and Flipped Classroom. The effectiveness of the sequence was evaluated through questionnaires applied before and after the didactic sequence, revealing a significant increase in students’ understanding of concepts related to the Geopark. The results indicated that active methodologies are effective in promoting meaningful and autonomous learning, preparing students to face environmental and social challenges. This study contributes to the advancement of environmental education and Geoeducation, offering insights into the practical application of these approaches in high school education.